Immobilization of Eversa Lipases on Hydrophobic Supports for Ethanolysis of Sunflower Oil Solvent-Free - Remonatto, Daniela [UNESP]; Oliveira, J. Vladimir; Guisan, J. Manuel; Oliveira, Débora; Ninow, Jorge; Fernandez-Lorente, Gloria (Springer Nature, 2022)
Lipases are an important group of biocatalysts for many industrial applications. Two new commercial low-cost lipases Eversa® Transform and Eversa® Transform 2.0 was immobilized on four different hydrophobic supports: Lewatit-DVB, Purolite-DVB, Sepabeads-C18, and Purolite-C18. The performance of immobilized lipases was investigated in the transesterification of sunflower oil solvent-free in an anhydrous medium. Interesting results were obtained for both lipases and the four supports, but with Sepabeads support the lipases Eversa showed high catalytic activity. However, the more stable and efficient derivative was Eversa® Transform immobilized on Sepabeads C-18. A 98 wt% of ethyl ester of fatty acid (FAEE) was obtained, in 3 h at 40ºC, ethanol/sunflower oil molar ratio of 3:1 and a 10 wt% of the immobilized biocatalyst. After 6 reaction cycles, the immobilized biocatalyst preserved 70 wt% of activity. Both lipases immobilized in Sepabeads C-18 were highly active and stable in the presence of ethanol. The immobilization of Eversa Transform and Eversa Transform 2.0 in hydrophobic supports described in this study appears to be a promising alternative to the immobilization and application of these news lipases still unexplored.
Keywords: Eversa® Transform; Eversa® Transform 2.0; Hydrophobic supports; Immobilization; Lipase; Solvent-free